Normative Divergence on Consensual Homosexuality: A Comparative Study of Islamic Criminal Law and Indonesian Positive Law - M. Nurul Irfan; Laila Palupi Rahmadani; Maskur Rosyid; Harapandi Dahri; Shalini Urteaga-Crovetto (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2025)
The criminalisation of liwāṭ in Islamic criminal law is grounded in a robust normative framework. However, it contains a dialectic between the determination of ḥudūd and the discretion of taʿzīr, with the principle that darʾ al-ḥudūd bi al-shubuhāt prevents criminalisation when there is doubt. In contrast, Indonesian positive law explicitly does not criminalise consensual same-sex relations between adults because the principle of legality requires the formulation of a written, clear, and definite criminal offence. This absence of norms is not a legislative omission but rather a policy choice that creates legal ambiguity as a control mechanism, achieved indirectly through other legal regimes. This study employs a normative and comparative juridical approach, focusing on the textual interpretation of Islamic criminal law and national statutory provisions. The results show that the tension between the certainty of criminalisation in Islamic criminal law and the ambiguity of Indonesian positive law illustrates two different models of social control: cautious normative certainty versus managed normative absence. The primary contribution of this research is to offer a new conceptual framework by repositioning the